1991
DOI: 10.1152/ajpregu.1991.261.2.r442
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between effects of interleukin-1 alpha administration and sublethal endotoxemia in primates

Abstract: Interleukin (IL)-1 is an early mediator of host response to inflammation, although its contribution to individual components of the acute phase reaction is still unclear. To evaluate how the hemodynamic, metabolic, and hormonal responses to sublethal endotoxemia compare with IL-1 administration, baboons received intravenously either lipopolysaccharide (LPS) or 0.1, 10, or 100 micrograms/kg IL-1 alpha. LPS induced an early tachycardia and a fall in mean arterial pressure, as well as lacticacidemia and hypoamino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1
4

Year Published

1992
1992
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 0 publications
1
47
1
4
Order By: Relevance
“…On day 2, arterial blood was obtained at 6:00 a.m. (i.e., directly before the start of the infusion of epinephrine in the EPI-3 group or the start of saline infusion in the control group) ( t ϭ Ϫ 3 h), directly before the injection of endotoxin ( t ϭ 0 h), and 0.5, 1, 1.5, 2, 3, 4,5,6,8,12, and 24 h thereafter. All blood samples (except samples for leukocyte counts) were centrifuged at 4 Њ C for 20 min at 1,600 g and stored at Ϫ 70 Њ C until assayed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On day 2, arterial blood was obtained at 6:00 a.m. (i.e., directly before the start of the infusion of epinephrine in the EPI-3 group or the start of saline infusion in the control group) ( t ϭ Ϫ 3 h), directly before the injection of endotoxin ( t ϭ 0 h), and 0.5, 1, 1.5, 2, 3, 4,5,6,8,12, and 24 h thereafter. All blood samples (except samples for leukocyte counts) were centrifuged at 4 Њ C for 20 min at 1,600 g and stored at Ϫ 70 Њ C until assayed.…”
Section: Methodsmentioning
confidence: 99%
“…It was therefore possible that epinephrine inhibits LPS-induced TNF production in whole blood at least in part by enhancing the release of IL-10. To test this hypothesis, we incubated whole blood for various time periods (4,8,12, and 16 h) with LPS (10 ng/ml) in the presence or absence of epinephrine (10 Ϫ6 M), a neutralizing anti-IL-10 mAb (25 g/ml) or an equivalent amount of an irrelevant isotype-matched control mAb. Anti-IL-10 potentiated LPSinduced TNF production, an effect that became significant after incubations of whole blood for 8 h or longer (Table I).…”
Section: Contribution Of ␣ and ␤ Adrenergic Receptors To Potentiationmentioning
confidence: 99%
“…We have recently reported that administration of recombinant human IL-la to healthy primates will result in hypotension and tachycardia similar to that seen in endotoxemia (6). Although quantities as low as 100 ng/kg body weight (BW) will produce significant tachycardia, 100 gg/kg BW of IL-la decreases cardiac output and causes adrenal cortex hemorrhage.…”
Section: Introductionmentioning
confidence: 96%
“…IL-1, -6, and -8 (23)(24)(25)(26), as well as TNF-lY, are also reduced during Il. -Lra administration (27), findings that may also account for the improvement in cardiac output and blood pressure in this model.…”
Section: Resultsmentioning
confidence: 99%